Workshop integrating care by payment reform; the case of Dutch birth care - Jeroen Struijs; Hester van Dorst; Eline de Vries (International Journal of Integrated Care, 2019)
Introduction: In 2017, the Dutch Ministry of Health introduced bundled  payments for birth care on a voluntary basis. This is designed to improve value by increased collaboration among midwives, gynecologists and other maternity care providers. Traditionally, these providers are reimbursed via a fee-for-service payment model. The new payment model aims to shift financial and clinical accountability to a new provider-led entity (a so called integrated birth care organization(ibco)) which functions as a general contractor. In that manner, bundled payments incentivize better coordination of care and reduce the incentives for overuse, duplicated services and low-value care.  Currently, within seven regions bundled payment contracts are signed and more contracts are expected in 2019. Objective: To give insight in:  1- the performance of ibco’s who implemented the payment reform versus regions who did not (in terms of health outcomes, utilization and spending) in the period prior to the payment reform, 2- the first experiences of implementing bundled payments  in the first year after the payment reform. Outline of the workshop (60+20 min) Performance of birth care organizations prior to the payment reform in terms of health outcomes, utilization and spending (presenter: EdV: 20+5 min) First, the national developments specific for the Dutch situation will be outlined. The early adapters differ from the birth care organization who did not implement bundled payments in 2017 in terms of birth care related spending and caesarean section and epidural rates, while no differences in health outcomes were observed. First experiences of bundled payments (presenter HvD (20+5 min)) Similarities and differences in the set-up of the first ibco will be laid out. This includes the development, content and implications of bundled payment contracts and the found ‘safety net clauses’ around tariffs. Importantly, boundaries for non-integrated birth care organisations and the contributions of bundled payment by experience of professionals in the field are highlighted. These insights are drawn from over 55 semi-structured interviews from all disciplines in and associated with birth care. At the end of the workshop, a discussion on international differences, development of quality indicators and implications of research findings will be encouraged. Fitting with the congress themes Building a stronger integrated primary care Defining measures and outcomes that matter to people Creating shared cultures, norms and values across organisations, professionals and people Learnings/take away messages: - An overview of processes leading to implementation of the first bundled payments in Dutch birth care - National database containing medical spending, health outcomes and quality on an individual level as a foundation for a virtual cohort - From data to knowledge, what does a combined database entail - To understand the Dutch bundled payment model for birth care and how this has been implemented - Insight in the key facilitators and barriers for implementing bundled payment for birth care